2021
DOI: 10.2174/1389450121999201013154542
|View full text |Cite
|
Sign up to set email alerts
|

Physcion and Physcion 8-O-β-D-glucopyranoside: Natural Anthraquinones with Potential Anticancer Activities

Abstract: : Nature has provided prodigious reservoirs of pharmacologically active compounds for drug development since times. Physcion and physcion 8-O-β-D-glucopyranoside (PG) are bioactive natural anthraquinones which exert anti-inflammatory and anti-cancer properties with minimum or no adverse effects. Moreover, physcion also exhibits anti-microbial and hepatoprotective properties while PG is known to have anti-sepsis as well as ameliorative activities against dementia. This review aims to highlight the natural sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 147 publications
(222 reference statements)
0
17
0
Order By: Relevance
“…AQs, including PTN, act inhibiting tumour growth and metastasis, inducing apoptosis and cancer cell metabolism, re-programmation and cell cycle arrest, regulating cell signalling pathways, and improving the effectivity of other chemotherapeutics in drug-resistant cells 35 . Whereas some authors demonstrated that PTN was significantly cytotoxic in the dark when it was used at concentrations from 50 μM onwards after 72 h exposure, with a low percentage of apoptotic cells 36 ; other authors demonstrated that lower exposure time to in vitro growing cells induced no significant effect on the inhibition of cancer cell proliferation (35 µM for 16 h 37 , and 40 and 80 µM for 12 h) 38 .…”
Section: Discussionmentioning
confidence: 99%
“…AQs, including PTN, act inhibiting tumour growth and metastasis, inducing apoptosis and cancer cell metabolism, re-programmation and cell cycle arrest, regulating cell signalling pathways, and improving the effectivity of other chemotherapeutics in drug-resistant cells 35 . Whereas some authors demonstrated that PTN was significantly cytotoxic in the dark when it was used at concentrations from 50 μM onwards after 72 h exposure, with a low percentage of apoptotic cells 36 ; other authors demonstrated that lower exposure time to in vitro growing cells induced no significant effect on the inhibition of cancer cell proliferation (35 µM for 16 h 37 , and 40 and 80 µM for 12 h) 38 .…”
Section: Discussionmentioning
confidence: 99%
“…AQs, including PTN, act inhibiting tumour growth and metastasis, inducing apoptosis and cancer cell metabolism, re-programmation and cell cycle arrest, regulating cell signalling pathways, and improving the effectivity of other chemotherapeutics in drug-resistant cells [34]. Whereas some authors demonstrated that PTN was signi cantly cytotoxic in the dark when it was used at concentrations from 50 µM onwards after 72 h exposure, with a low percentage of apoptotic cells [35]; other authors demonstrated that lower exposure time to in vitro growing cells induced no signi cant effect on the inhibition of cancer cell proliferation (35 µM for 16 h [36], and 40 and 80 µM for 12 h) [37].…”
Section: Discussionmentioning
confidence: 99%
“…Physcion also modulates cancer cell metabolism. In particular, it inhibits the 6-phosphogluconate dehydrogenase (6PGD) enzyme, usually overexpressed in cancer cells [ 89 ].…”
Section: Anticancer Mechanisms Of Aqs Isolated From Marine Fungimentioning
confidence: 99%